A heat shock process for the puffing of dried food gels : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology in Food Chemistry and Engineering at Massey University of Manawatu, Palmerston North, New Zealand - Perreau, Rex George (Massey University, 1965)
There has been increasing interest in recent years in the use of dehydration as a technique for the preservation of foodstuffs. An extract of production figures compiled by Van Arsdel (1963) is given in Table (l). The production per year, in tons, of six dehydrated foods in the United States of America is shown and indicates this trend which is particularly marked in the production of dried potatoes (mainly instant mashed potatoes), and non-fat milk solids.[FROM INTRODUCTION]
Keywords: Colloids -- Effect of temperature on; Food industry and trade; Technology